Answer:
Simplifying
2x + -5 = x + -4
Reorder the terms:
-5 + 2x = x + -4
Reorder the terms:
-5 + 2x = -4 + x
Solving
-5 + 2x = -4 + x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
-5 + 2x + -1x = -4 + x + -1x
Combine like terms: 2x + -1x = 1x
-5 + 1x = -4 + x + -1x
Combine like terms: x + -1x = 0
-5 + 1x = -4 + 0
-5 + 1x = -4
Add '5' to each side of the equation.
-5 + 5 + 1x = -4 + 5
Combine like terms: -5 + 5 = 0
0 + 1x = -4 + 5
1x = -4 + 5
Combine like terms: -4 + 5 = 1
1x = 1
Divide each side by '1'.
x = 1
Simplifying
x = 1